Electronic transport properties of electrically doped cytosine‐based optical molecular switch with single‐wall carbon nanotube electrodes. Issue 5 (17th April 2019) - Dey, Debarati; Roy, Pradipta; De, Debashis
Abstract : This study represents an empirical model of cytosine‐based optical molecular switch. This possible biomolecular switch has been designed using the first principle approach which is based on density functional theory and non‐equilibrium Green's function. The quantum‐ballistic transport property and current–voltage (I–V) characteristics of cytosine‐based optomolecular switch have been investigated at 25 THz operating frequency. The influence of highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) gaps on the electronic transmission and I–V characteristics has been discussed in detail. The aim of this study is to highlight the minimum conformational change during a single ON–OFF switching cycle. The biomolecule comprises switching behaviour when converts from straightened to twisted form during photo‐excitement. The straightened and twisted forms of the molecule are represented as logic '0' and logic '1', respectively. This p and n regions of this switch has been made using electrical doping process. The current through the twisted form of the cytosine biomolecule is ∼1000 times higher than the straightened form. The maximum switching ratio 62.1 is obtained at 1 V bias. The origin of the switching behaviour of the biomolecule can be interpreted by quantum–ballistic transport model along with HOMO–LUMO gaps.